ET ZEBRASTRIBET CIRKUSNUMMER: Om latterens scenarium - Hansen, Helle Ploug (Tidsskriftet Antropologi, 1997)
Helle Ploug Hansen: A Zebra-Striped Circus Performance. The Scenario of Laughter This article looks at humour and laughter as a complex social and cultural phenomenon. It is based on a description of a circus performance in Copenhagen in which a plastic zebra, after having read a zebrastriped book, lay down on the scene in the performance hall. The performance is first analysed as a parody of a traditional circus performance and as an absurd form of humour. The article then focuses on laughter as a spontaneous answer from the body to an unknown and unpredictable phenomenon. Finally Bateson’s theory of communication is introduced in order to understand humour and laughter as a meta-communicative manifestation, that comments upon and challenges the social order.